Plebiscites in Europe after the First World War - Osojnik, Janez (Studia Historica Slovenica, 2021)
The article discusses plebiscites held in years after the First World War, specifically in 1920 and 1921. They were conducted for the purpose of redrawing borders in areas where this was difficult due to their multinational structure, as well as economic, geographical, and historical factors. Thus, the great powers, who were on a winning side in the First World War, in some cases decided for an instrument of popular vote, which was not a novelty in history, but was then used for the first time to a greater extend. In the article, the authors present the similarities and differences between the discussed plebiscites.
Keywords: Avstrijska Koroška; diplomacija; diplomacy; državne meje; Klagenfurt basin; Kwidztyn / Marienwerder; Kwidzyn/Marienwerder; mirovne konference; Olsztyn / Allenstein; Olsztyn/Allenstein; Paris Peace Conference; plebiscite; plebiscite commission; plebisciti; politična zgodovina; Schleswig; Sopron; Svetovna vojna 1914-1918; Šopron; Upper Silesia; Zgornja Šlezija